Endoftalmitis Okuli Dextra pada Seorang Pekerja Konstruksi : Laporan Kasus - Almaina Puteri Jasmine; Risti Graharti; Rani Himayani (Medula, 2026)
Endophthalmitis is a severe intraocular infection involving the aqueous and/or vitreous humor and is considered an ophthalmic emergency due to its potential to cause irreversible vision loss if not treated promptly. Globally, most cases of endophthalmitis are associated with ocular surgery and ocular trauma. Exogenous endophthalmitis is the most common form and may be caused by Gram-positive bacteria, Gram-negative bacteria, or fungi. Ocular trauma is one of the major risk factors for the development of exogenous endophthalmitis. This report describes a 49-year-old construction worker presenting with right eye redness, pain radiating to the head, swelling, and progressive visual deterioration leading to loss of light perception. Ophthalmologic examination revealed no light perception in the right eye, eyelid edema and hyperemia, mucoserous discharge, conjunctival injection, corneal opacity, and hypopyon involving up to three-quarters of the cornea. The patient was diagnosed with right eye endophthalmitis and treated with topical levofloxacin, ceftriaxone, methylprednisolone, and ketorolac. After two days of treatment, no clinical improvement was observed. The patient was subsequently scheduled for surgical evisceration. This case highlights that endophthalmitis may present with severe clinical manifestations and poor outcomes in advanced stages. Prompt diagnosis and appropriate management are essential to preserve visual function and prevent further complications.